Potential role of transgenic approaches in the control of cowpea insect pests - Machuka, J. (2002)
Crops' incompatibility makes conventional breeding approaches untenable in transferring available insect resistance From wild Vigna sp. into cowpea. The alternative recourse is to isolate and transfer alien resistance genes using genetic transformation. This has the added advantage of using useful genes from distantly related organisms to control cowpea pests. Artificial diet bioassays carried out on the Maruca pod borer, pod sucking bugs, and cowpea weevils indicate that these insects can be controlled by Bacillus thuringiensis crystal proteins, plant lectins, protease, a-amylase inhibitors, chitinascs, and/or ribosome-inactivating proteins. The challenge now is to express the genes encoding these proteins in transgenic cowpea and hope that what happens in artificial diets will, at least in some cases, be replicated in transgenics. Other candidate genes include enzymes encoding biochemical pathways in secondary metabolism. It can be anticipated that useful information emerging from current global genomics efforts in crop species, including model legumes, will have a bearing on cowpea improvement through genetic engineering. What cowpea researchers need to do now is develop a comprehensive pest resistance management strategy. Such a strategy must take into account criteria such as transformation of elite cowpea lines that are adapted to each of